Rekonfigurasi Studi Hadis pada Perguruan Tinggi Keagamaan Islam di Indonesia antara Tradisi Keilmuan dan Standar Akademik Global - Lukman Zain; Anisatun Muthi'ah; Alwi Bani Rakhman; Ahmed Abdul Malik (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Even though the Hadith has a central position as the second main source of Islamic knowledge after the Qur’an, Hadith studies remain marginalized in many Indonesian Islamic universities, often overshadowed by Qur’anic exegesis, Islamic law, and Sufism. This study examines how three leading State Islamic Universities, UIN Sunan Kalijaga Yogyakarta, UIN Sunan Gunung Djati Bandung, and UIN Alauddin Makassar, have strategically reconfigured their Hadith Science departments in response to both internal demands for academic quality and external pressures from global educational standards. These universities were selected due to their institutional prominence, academic innovations, and representative models of transformation within Indonesia’s State Islamic Religious Higher Education system. This study explores the following questions: (1) how are Hadith Studies departments reconfigured institutionally and academically within these universities? and (2) how do these transformations negotiate between Islamic scientific tradition and global academic standards? Employing qualitative methods, including in-depth interviews, policy and document analysis, and field observations, the research identifies four key drivers of revitalization: curricular reform aligned with the KKNI and MBKM frameworks, leadership-driven institutional transformation, integration of digital technologies in Hadith pedagogy, and the establishment of collaborative networks with governmental bodies, religious communities, and international partners. Using a multidisciplinary approach, and drawing primarily on functionalist social theory and Islamic epistemology, the findings reveal that these reforms represent not only academic transformation but also an epistemic negotiation that reconciles religious authenticity with the methodological rigor and global relevance demanded by modern higher education. By harmonizing ʿaqlī (rational) and naqlī (transmitted) traditions, reclaiming intellectual sovereignty through localized innovation, and reorienting curriculum and research practices, this study offers a replicable model for advancing Islamic sciences in other Islamic academic institutions by fostering dialogue between scholarly tradition and contemporary innovation.